2020
DOI: 10.7717/peerj.9409
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial stewardship in remote primary healthcare across northern Australia

Abstract: Background The high burden of infectious disease and associated antimicrobial use likely contribute to the emergence of antimicrobial resistance in remote Australian Aboriginal communities. We aimed to develop and apply context-specific tools to audit antimicrobial use in the remote primary healthcare setting. Methods We adapted the General Practice version of the National Antimicrobial Prescribing Survey (GP NAPS) tool to audit antimicrobial use over 2–3 weeks in 15 remote primary healthcare clinics across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…While this study portrayed a positive outlook in Australia, the results cannot be generalised as the focus was on early-career general practitioners and urinary tract infections only, and rural practices constituted only 16% of the study locations [ 40 ]. An audit of antimicrobial use in 15 remote PHC clinics across three states in northern Australia found that appropriateness was high compared to general practices in urban settings [ 45 ]. Approximately 91%, 82% and 65% of antimicrobial use in Western Australia, Northern Territory and Queensland adhered to clinical guidelines, endorsed by experts, or constituted agents with the narrowest targets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While this study portrayed a positive outlook in Australia, the results cannot be generalised as the focus was on early-career general practitioners and urinary tract infections only, and rural practices constituted only 16% of the study locations [ 40 ]. An audit of antimicrobial use in 15 remote PHC clinics across three states in northern Australia found that appropriateness was high compared to general practices in urban settings [ 45 ]. Approximately 91%, 82% and 65% of antimicrobial use in Western Australia, Northern Territory and Queensland adhered to clinical guidelines, endorsed by experts, or constituted agents with the narrowest targets.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 91%, 82% and 65% of antimicrobial use in Western Australia, Northern Territory and Queensland adhered to clinical guidelines, endorsed by experts, or constituted agents with the narrowest targets. This appreciably high level of appropriateness was demonstrated by 86% of nurses and 73% of doctors in this region [ 45 ]. The high rates of appropriateness in this study may be a result of government endorsed clinical guidelines that the nurses are legally bound to comply with in order to prescribe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If these resources were available, CPs could be more engaged in performing antimicrobial audits, reviewing antimicrobial prescriptions, and providing feedback to GPs. In Australia, a tool [38] to audit antimicrobial use in the context of remote primary healthcare has been tested and this tool could be integrated into clinical practice in future.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study internationally that compares and contrasts the views of GPs and CPs about the collaborative implementation of AMS, both quantitatively and qualitatively, through two nationwide surveys. In the hospital settings, there is much evidence for strong physician-pharmacist collaboration for effective implementation of AMS programs [38,39]. In contrast, this study is very important because the hospital collaborative model is not feasible in the primary care setting, and the results will assist the design of such a model in primary care.…”
Section: Strengthsmentioning
confidence: 98%